Key factors predicting suspected severe malaria case management and health outcomes: an operational study in the Democratic Republic of the Congo - Jean Okitawutshu; Aita Signorell; Jean-Claude Kalenga; Eric Mukomena; Giulia Delvento; Christian Burri; Fatou Mwaluke; Valentina Buj; Moulaye Sangare; Sylvie Luketa; Nina Brunner; Tristan Lee; et al. (Malaria Journal, 2022)
Abstract Background Evidence suggests that pre-referral Rectal Artesunate (RAS) can be a life-saving intervention for severe malaria in remote settings in Africa. Recognition of danger signs indicative of severe malaria is critical for prompt and appropriate case management. Methods This was an observational study conducted in three Health Zones of the Democratic Republic of the Congo to determine the distribution of dangers signs for severe malaria and assess their impact on RAS use, referral completion, injectable treatment and ACT provision, and health outcomes including death. An individual-level analysis was carried out, using multilevel-mixed effects logistic regression models. Severely ill febrile children < 5 years seeking care from community-based healthcare providers were recruited into a patient surveillance system based on the presence of key danger signs. Clinical and case management data were collected comprehensively over a 28 days period. Treatment seeking was elicited and health outcomes assessed during 28 days home visits. Results Overall, 66.4% of patients had iCCM general danger signs. Age of 2–5 years and iCCM general danger signs predicted RAS use (aOR = 2.77, 95% CI 2.04–3.77). RAS administration positively affected referral completion (aOR = 0.63, 95% CI 0.44–0.92). After RAS rollout, 161 children died (case fatality ratio: 7.1%, 95% CI 6.1–8.2). RAS improved the health status of the children on Day 28 (aOR = 0.64, 95% CI 0.45–0.92) and there was a non-significant trend that mortality was higher in children not receiving RAS (aOR = 1.50, 95% CI 0.86–2.60). Full severe malaria treatment at the RHF including injectable anti-malarial and a course of ACT was highly protective against death (aOR = 0.26, 95% CI 0.09–0.79). Conclusions The main findings point towards the fact that danger signs are reasonably well recognized by health provider at the primary care level, and that RAS could influence positively health outcomes of such severe disease episodes and death. Its effectiveness is hampered by the insufficient quality of care at RHF, especially the provision of a full course of ACT following parenteral treatment. These are simple but important findings that requires urgent action by the health system planners and implementers.